Effects of carbohydrate content on body composition during weight loss in female fitness competitors - Luotonen, Inga (2017)
Introduction. Bodybuilders and fitness competitors are aiming to reduce fat mass and maintain lean mass during the competition phase. Low carbohydrate diets compared to low fat diets have claimed to be more effective in weight loss, but the results are still controversial. Low carbohydrate intake and high protein intake have been reported in bodybuilders during the diet, but the evidence of its effectiveness is limited. The aim of this study was to examine the effects of carbohydrate content on body composition during weight loss in female fitness competitors. Methods. A total of 50 female subjects participated in this study, 27 were competitors, and 23 were weight training stable controls. Twelve of the competitors were followed with relatively low carbohydrate (LC) to high carbohydrate (HC) diets. The HC group included six subjects (mean ± SD; age 27.5 ± 4.4 y, weight 64.8 ± 4.4 kg, and height 1.65 ± 0.03 m), whose carbohydrate intake during the weight loss was set > 145 g/d, and the proportion from the energy less than 7 % decrease from the baseline. The LC group included six subjects (mean ± SD; age 29 ± 3.3 y, weight 63.9 ± 7.7 kg and height 1.64 ± 0.06 m), and the values for carbohydrate intake during weight loss was < 120g/d, and the proportion from the energy at least 10 % decrease from the baseline. Nutritional data was analyzed based on the food diaries by nutrient analysis software (Aivodiet, Flow-team Oy, Oulu, Finland). The body composition was measured at two time points, before the diet and the day after the competition. The body composition was measured by both InBody bioimpedance and Dual Energy X-ray absorptiometry (DXA). Muscle cross sectional area of vastus lateralis (VL) muscle and thickness of triceps brachii (TB) muscle was measured using ultrasound. The energy expenditure was calculated by activity diaries as MET-hours and training frequency. Results. The energy intake was significantly lower in the LC group than in the HC group during the diet (P=0.002), similarly the absolute carbohydrate intake (P=0.001), per kg body weight (P=0.002) and relative (P=0.02) was lower in LC. Protein intake was absolutely (P=0.03) and per kg body weight (P=0.04) lower in the LC group. Fat intake decreased slightly in both groups, but the relative intake decreased only in LC (P=0.05). Fat mass decreased in both groups as measured with all methods, but the loss was not significant between the groups. Fat in VL decreased more in the HC group (P=0.006) compared to the LC group (P=0.05), but was not significant between the groups (P=0.47). No significant change between the groups in fat or thickness of TB was observed. The VL CSA decreased in the LC group by 2.8 cm2 (P=0.023) and increased in the HC group by 0.9 cm2 (P=0.25), but the VL CSA was greater in the LC group at the baseline (P=0.005). Lean mass slightly increased during the diet in both groups when measured by DXA, but LBM remained unchanged, when measured by InBody bioimpedance. Conclusion. The main finding of the study was that there were no consistent effects between the low and high CHO groups in the body composition and muscle or fat size changes. However, there were few differences between the groups. Fat mass decreased in both groups, but the VL CSA decreased only in the LC group compared to the HC group who even managed slightly to increase muscle size in front thighs. The findings support the fact that the energy deficit is the most important thing in weight loss rather than macronutrient content. It might be that normal carbohydrate with high protein intake would provide better outcomes in weight loss in female fitness competitors, for sparing muscle size at least in thighs, but the future investigation is needed.